2020
DOI: 10.3389/fneur.2020.00127
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Contribution to Motor and Non-motor Functions in Parkinson's Disease: A Meta-Analysis of fMRI Findings

Abstract: Background: Parkinson's disease (PD) results in both motor and non-motor symptoms. Traditionally, the underlying mechanism of PD has been linked to neurodegeneration of the basal ganglia. Yet it does not adequately account for the non-motor symptoms of the disease, suggesting that other brain regions may be involved. One such region is the cerebellum, which is known to be involved, together with the basal ganglia, in both motor and non-motor functions. Many studies have found the cerebellum to be hyperactive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 131 publications
2
29
0
Order By: Relevance
“…Cerebellar hyperactivity and hyperconnectivity have been reported in task-based and resting-state fMRI studies of PD (Helmich et al, 2011, Wu and Hallett, 2013, Festini et al, 2015 and generally attributed to compensatory mechanisms. This functional pattern was most consistently exhibited in PD subjects scanned off dopaminergic medication and was either normalized or even reduced by medication (Festini et al, 2015;Solstrand Dahlberg et al, 2020). Moreover, different cerebellar lobules have been found to display diverse activation and connectivity characteristics in PD depending on the motor, emotional, and cognitive context (Solstrand Dahlberg et al, 2020) as we have also observed in our motor and nonmotor network data.…”
Section: Discussionsupporting
confidence: 76%
“…Cerebellar hyperactivity and hyperconnectivity have been reported in task-based and resting-state fMRI studies of PD (Helmich et al, 2011, Wu and Hallett, 2013, Festini et al, 2015 and generally attributed to compensatory mechanisms. This functional pattern was most consistently exhibited in PD subjects scanned off dopaminergic medication and was either normalized or even reduced by medication (Festini et al, 2015;Solstrand Dahlberg et al, 2020). Moreover, different cerebellar lobules have been found to display diverse activation and connectivity characteristics in PD depending on the motor, emotional, and cognitive context (Solstrand Dahlberg et al, 2020) as we have also observed in our motor and nonmotor network data.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, a meta-analysis of task-related fMRI studies has emphasized that the cerebellum plays a significant role in the level of cognitive functioning in PD ( 16 ). Moreover, Gao et al ( 44 ) has shown that the performance of PD patients and healthy control subjects do not differ significantly when required to execute motor and cognitive dual-task paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of a “motor” cerebellum including lobules V, VI, VIIb, and VIII as well as of a “cognitive” cerebellum including crus I and II supports this functional cerebellar dissociation ( 9 , 12 , 15 , 18 , 19 ). A recent meta-analysis has also reported cerebellar hyperactivations in PD patients who were administered cognitive or motor paradigms with significant cognitive task demands, hence suggesting that one of the main cerebellar implications in PD is linked to cognitive functioning ( 16 ). Finally, using structural and resting-state functional magnetic resonance imaging (rs-fMRI), O'Callaghan et al ( 20 ) revealed gray matter loss across the “motor” and “cognitive” cerebellar territories and altered cerebellar functional connectivity (FC) with the cortex in patients with PD compared to normal controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although social deficits in PD have been related to dopamine depletion in these nuclei ( Coundouris et al, 2019 ), particularly in the putamen ( Palmeri et al, 2017 ), alterations in the functioning of other brain regions may contribute to the impairment. Among these, the cerebellum – which is known to be involved in cognitive processing beyond motor control ( Hull, 2020 , Schmahmann et al, 2019 ) - may play a critical role ( Solstrand Dahlberg et al, 2020 ). Indeed, abnormal cerebellum activity has been observed in PD patients during both cognitive (e.g., Cao et al, 2011 , Huang et al, 2007a , Huang et al, 2007b ) and social perception (e.g., Poisson et al, 2013 ) tasks, as well as during rest conditions (e.g., Zhan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%